Exploration of Modulation Index in Multi-level Inverter using Particle Swarm Optimization Algorithm - Ali, S.S.A. (Elsevier B.V., 2017)
This research paper describes the Particle Swarm Optimization algorithm real with Selective Harmonic Elimination-Pulse Width Modulation (SHEPWM) method for harmonic minimization of Cascaded H-Bridge Multi-Level Inverter. In SHEPWM method- PSO algorithm is capable of determining the required switching angles to eliminate desired value of harmonics. The value of harmonics may reach up to the 11th order from the inverter output voltage waveform while keeping the magnitude of the funda- mental harmonics at a certain value. Hence, the proposed method does capable of eliminating a great number of specific harmonics and the output voltage results in a minimum Total Harmonic Distortion value. The simulation results shows that the PSO algorithm successfully attains the global solution faster than other algorithms. © 2017 The Authors.